The Pengaruh Internal Audit Dan Whistleblowing System Terhadap Pencegahan Fraud Dengan Moralitas Individu Sebagai Variabel Moderator (Studi Empiris Pada Bank Perkreditan Rakyat Di Provinsi Riau) - Dewi Sartikah Putri Harahap; Nasrizal Nasrizal; Novita Indrawati; Siti Hanifa Sandri (Akuntansi & Ekonomika, 2022)
The purpose of this study is to examine the internal audit and whistleblowing system as independent variables, fraud prevention as the dependent variable and individual morality as a moderating variable. The data in this study were taken with using a questionnaire that was distributed throughout BPR in Riau Province. Collected from 29 BPR in Riau Province, the respondents of this study consisted of each BPR internal audit section and finance department with a total amount of the total respondents were 87 people. The data analysis technique used in this research is Partial Least Square (PLS) with the help of WarpPls 7.0 software. The results of this study indicate that internal audit and the whistleblowing system have an effect on fraud prevention and individual morality moderates the relationship between internal audit and the whistleblowing system on fraud prevention.